Electrochemical Aptasensor for Rapid and Sensitive Determination of Salmonella Based on Target-Induced Strand Displacement and Gold Nanoparticle Amplification. (12th October 2016) - Li, Xiaolu; Fu, Hu; He, Yun; Zhai, Qian; Guo, Jing; Qing, Keqin; Yi, Gang
ABSTRACT: A simple, rapid, and sensitive electrochemical aptasensor based on target-induced strand displacement and gold nanoparticle amplification was developed for the determination of Salmonella . The aptamer for Salmonella was captured on the sensing interface by hybridizing with a capture probe. In the presence of Salmonella, the aptamer dissociated from the capture probe as the stronger interaction between the aptamer and the Salmonella . The single-strand capture probe was then hybridized with the biotinylated detection probe assembled on gold nanoparticles and catalyzed by streptavidin–alkaline phosphatase, providing a sensitive electrochemical response. The gold nanoparticles significantly amplified the detection probe signal and increased the sensitivity. The linear dynamic range was from 2 × 10 1 to 2 × 10 6 CFU mL −1 with a detection limit of 20 CFU mL −1 . This strategy was utilized for the determination of Salmonella in milk, demonstrating potential application in clinical diagnostics, food safety, and environmental monitoring.